Vouchers for Health : Using Voucher Schemes for Output-Based Aid - Sandiford, Peter; Gorter, Anna; Salvetto, Micol (World Bank, Washington, DC, 2012)
This Note examines an innovative, donor-supported voucher scheme to treat and prevent sexually transmitted diseases in Nicaragua. Voucher schemes enable donors to purchase outputs rather than inputs while also offering beneficiaries a choice of provider, a feature that sets them apart from other output-based approaches, such as supply-side subsidies to providers operating under performance-based contracts. Choice creates incentives to lower prices or raise quality (or both).